Neurofibromatosis type 1 in two siblings due to maternal germline mosaicism. (27th May 2013) - Trevisson, E.; Forzan, M.; Salviati, L.; Clementi, M.
<x xml:space="preserve">Abstract</x> Neurofibromatosis type 1 (NF1) is caused by loss of function mutations of the NF1 gene, which are de novo in 50% of cases. Although this gene shows one of the highest mutation rates in the human genome, germline mosaicism is very rare in this condition. We describe the molecular analysis of a family in which neurofibromatosis type 1 occurred in two out of four siblings born to unaffected parents. Molecular analysis of the NF1 gene identified in both patients the same splicing mutation c.1392+1G>A, which was absent in parental lymphocytes. Microsatellite analysis showed that the two affected siblings shared the same maternal allele, however a specific PCR‐RFLP assay excluded the presence of the NF1 splicing mutation in multiple maternal tissues. Our molecular and clinical findings are consistent with a germline mosaicism for the NF1 splicing mutation. This is the first case of maternal germline mosaicism for a NF1 mutation characterized so far at the molecular level. Our data confirm that germline mosaicism is rare in neurofibromatosis 1, but it has important implications for genetic counseling.